2022
DOI: 10.3390/su14020987
|View full text |Cite
|
Sign up to set email alerts
|

International Research Progress and Evolution Trend of Interpersonal Trust—Prospects under COVID-19 Pandemic

Abstract: Retrospecting articles on interpersonal trust is of great importance for understanding its current status and future development in the context of the COVID-19 pandemic, especially, with the widespread use of Big Data and Blockchain. In total, 1532 articles related to interpersonal trust were collected as research database to draw keyword co-occurrence mapping and timeline mapping by VOSviewer and CiteSpace. On this basis, the research content and evolution trend of interpersonal trust were systematically anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Our results suggested that SSG also has an important instrumental function. In addition, a systematic review of research in the context of COVID-19 revealed that Chinese Guanxi is worthy of extensive exploration (Ji and Long, 2022). Our findings not only support previous research (Ali et al , 2020; Cheung and Wu, 2011; Weng, 2014), but also clarify the moderating role of SSG in the relationship between emotional labor and service quality.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our results suggested that SSG also has an important instrumental function. In addition, a systematic review of research in the context of COVID-19 revealed that Chinese Guanxi is worthy of extensive exploration (Ji and Long, 2022). Our findings not only support previous research (Ali et al , 2020; Cheung and Wu, 2011; Weng, 2014), but also clarify the moderating role of SSG in the relationship between emotional labor and service quality.…”
Section: Discussionmentioning
confidence: 99%
“…Our results suggested that SSG also has an important instrumental function. In addition, a systematic review of research in the context of COVID-19 revealed that Chinese Guanxi is worthy of extensive exploration (Ji and Long, 2022).…”
Section: Theoretical Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The combined influence of two factors-the phenomenon of infodemia and the reaction of society to the actions of governments during the pandemic-has not yet been sufficiently covered by scientific research. The impact of the credibility factor, in particular, of interpersonal trust dynamics during the COVID-19 pandemic is shown in the research [7] with extensive use of big data and blockchain. The present study focuses on the impact that mass media and opinion leaders have on the users of social media.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, higher economic growth does not always promote higher interpersonal trust (Helliwell, 1996;Inglehart, 1997;Olson, 1982). One rationale for such is that the role of interpersonal trust is higher in developing and less developed countries (Ji & Long, 2022). On the other hand, literature has also established that interpersonal trust and trustworthiness is a keystone towards higher economic development (Banfield, 1967;Coleman, 1988;Dasgupta & Gambetta, 1988;Fukuyama, 1995;Greif, 1993;Putnam, 2000).…”
Section: Introductionmentioning
confidence: 99%